Ответы и объяснения

  • Sky09
  • профессор
2013-06-15T15:48:24+04:00

\frac{2+x-x^2}{2-5x+3x^2}+\frac{10x}{3x-2}=\frac{2+x-x^2}{(x-1)(3x-2)}+\frac{10x}{3x-2}=

 

=\frac{2+x-x^2+10x(x-1)}{(3x-2)(x-1)}=\frac{2+x-x^2+10x^2-10x}{(3x-2)(x-1)}=

 

=\frac{9x^2-9x+2}{(3x-2)(x-1)}=\frac{(3x-2)(3x-1)}{(3x-2)(x-1)}=\frac{3x-1}{x-1}

 

***

Теперь отдельно разложения уравнений, чтобы было предельно ясно.

 

2-5x+3x^2=0;

D=25-24=1;

 x_1=1; x_2=\frac{2}{3}

2-5x+3x^2=3(x-1)(x-\frac{2}{3})=(x-1)(3x-2)

 

 

9x^2-9x+2=0

D=81-72=9

x_1=\frac{1}{3}; x_2=\frac{2}{3}

9x^2-9x+2=9(x-\frac{1}{3})(x-\frac{2}{3})=(3x-2)(3x-1)